Optimization of electric car motion on a horizontal rectilinear section of road by the criterion of mini-mum energy rechargeable battery - Mokin, O. B.; Mokin, B. I.; Foliushniak, O. D.; Lobatiuk, V. A. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Optimization of motion of the unloaded electric car is carried out with the hauling electric motor of direct-current of successive excitation on the horizontal rectilinear segment of road on the criterion of minimum of expenses of energy of storage battery. Mathematical model is built for a current in a chain: a storage battery is a puttee of anchor of hauling electric engine of direct-current series-wound, realization of that allows to minimize the expenses of energy of storage battery during motion on any law changes speed electric vehicle